Comparative blood parasites in boer goats reared under intensive and semi-intensive systems - Said, Cik Nasriah (2015)
A study was conducted to compare the prevalence of blood parasites in 38 Boer goats raised in two farms in Selangor practicing two management systems: intensive and semi-intensive. Age group and sex of each goat were determined during blood sampling. Blood samples were obtained from the jugular vein of the goats, smeared and examined under light microscope (100X) in oil immersion. Results showed there were no significant difference on the prevalence of blood parasites between the two management systems (p=0.232), sex of goats (p=0.363), and age groups (p=0.106). The overall prevalence rate of blood parasites in the two farms was 21.1% with 5.3% in intensive management system and 15.8% in the semi-intensive management system. The prevalence rate was found to be higher in the young and adult female goats compared with adult male goats. Therefore, it could be concluded that blood parasites can infect equally the Boer goats at any age group, sex and management system.